Before the wind [compact disc, unabridged] - Lynch, Jim, 1961- (Highbridge/Tantor Media, 2016)
" Growing up on the Puget Sound, the Johannssen family has sailing in their blood, but the olderst brother, Josh, is left puzzling over what caused his siblings to flee, one to Africa, the other to points unknown as a fugtitive and a pirate"--Back cover.